Cytotoxic Activity Of Isolated Alkaloids From The Bark Of Kopsia Terengganensis (Apocynaceae) And Corrosion Inhibition Studies Of Its Extract - Hanafi, Wan Nur Huda Wan (2023)
The use of natural products in developing chemotherapy agents has shown a positive impact in the oncology field. Besides, they also showed a significant result as a corrosion inhibitor. Hence, this study aims to evaluate the cytotoxic activity and corrosion inhibition potential of the crude extract and isolated alkaloids from Kopsia terengganensis (K. terengganensis). The experimental involved extraction and isolation of alkaloids using different chromatographic methods, structural elucidation using various chromatographic techniques and evaluation of cytotoxic activity on HT-29 colorectal adenocarcinoma. Meanwhile, corrosion inhibition studies included weight loss studies, electrochemical studies, and surface analysis. The extraction and isolation process resulted in seven alkaloid compounds: eburnamine (90), isoeburnamine (58), eburnaminol (99), larutensine (100), eburnamenine (114), eburnamonine (56) and quebrachamine (148). In the cytotoxic activity, only compound 99 was able to suppress the growth of HT-29 with moderate activity (IC50 =75.8± 3.06 μM). For the corrosion inhibition potential, the alkaloid crude showed significant results (80-90% inhibition efficiency) in both weight loss and electrochemical studies. The inhibitor followed the Langmuir adsorption isotherm and the formation of an inhibitive film on the mild steel surface was proved in the surface analysis. In conclusion, the alkaloids from K. terengganensis were noteworthy to be investigated in both cancer and corrosion inhibition studies as it gives a positive result in the toxicity towards cancer cells and also mitigated the mild steel corrosion.